Altered brain–behavior coupling during inhibitory control in ankylosing spondylitis: ERP evidence from NoGo-P3 component - Lei Zhang; Fang Lu; Yuxin He; Lin Tang; Li Zhang; Jing Xiang; Chun rong Gu; Su wan Guo; Zheng hong Yu (PLoS ONE, 2026)
Background Cognitive dysfunction has increasingly been recognized in Ankylosing Spondylitis (AS), yet the neural mechanisms underlying inhibitory control in this population remain insufficiently characterized. Rather than reflecting a simple global deficit, cognitive alterations in AS may involve task-dependent changes in the coupling between neural activity and behavioral performance. This study examined executive control in AS using a Go/NoGo paradigm and focus on brain-behavior coupling during inhibitory processing. Methods 16 male patients and 23 age-matched healthy controls completed a Go/NoGo task while undergoing 32-channel EEG recording. ERP analyses focused on N2 (200–300ms) and the late positive component in the NoGo condition (hereafter termed NoGo-P3; 400–600ms). Mean amplitudes were extracted at fronto-parietal midline electrodes. To directly test group differences in brain–behavior coupling, linear regression models including the ERP × Group interaction term were fitted. Theta-band (4–7 Hz) power within the 400–600 ms window was additionally analyzed using FFT-based spectral estimation. Results Behaviorally, AS patients showed lower Go accuracy and longer Go reaction times, together with a tendency toward higher NoGo accuracy. In AS patients, NoGo accuracy positively correlated with NoGo-P3 amplitude at FCz (r = .64, p = .009) and Cz (r = .55, p = .035), whereas these associations were not significant in controls. Direct group comparison showed a significant ERP × Group interaction at FCz (b = 0.084, p = 0.033), indicating that the relationship between NoGo-P3 amplitude and inhibitory accuracy differed between AS patients and healthy controls, while Cz (b = 0.051, p = 0.106) showed a similar but non-significant trend. Complementary theta analyses revealed enhanced post-stimulus theta power in centro-parietal regions during NoGo processing in AS. Conclusions The findings suggest altered brain–behavior coupling during inhibitory control in AS, with the most robust evidence emerging from the NoGo-P3 component at FCz. This pattern is consistent with greater reliance on effortful control-related neural recruitment during successful inhibition and may represent a candidate electrophysiological marker of altered executive processing in AS.